Hubungan Konsep Diri dan Behavior Regulation pada Mahasiswa UKM Dansa Universitas Indonesia - Lidwina Sonia A.; Bagus Takwin (Fakultas Psikologi Universitas Pancasila, 2010)
Today, one of the growing sport activities in Indonesia is dancing. As a new sport, dancing is lack of athlete who is able to represent Indonesia in international dancing competitions. This happens because dancing has been labeled as an expensive sport (Zadli, 2009). In fact, the qualification to become a dancer is strong physical and mental capability gained from regular and consistent trainings. One of the factors which may encourage someone to take regular trainings is motivation. A study conducted by Li et. al. (Batia, 2007) reveals that motivation may regulate desire and consistency to take regular trainings. Motivation types based on self-determination continuum are called behavior regulation. Ryan and Brown (in Magnus, 2007) mention that motivation type or behavior regulation is influenced by self-esteem, which is an aspect of self-concept. Hence, if self-esteem affects behavior regulation, self-concept may indirectly influence behavior regulation. The result of this study shows that there is no significant relationship between self-concept and behavior regulation in dancing because each respondent has different competition experience, and respondents hold a high self-concept. Thus, the respondent's motivation to practice dancing is not caused by high self-concept.